Proceedings of the 31st ACM International Conference on Design of Communication 2013
DOI: 10.1145/2507065.2507066
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the process of learning touch-screen mobile applications

Abstract: Mobile devices, together with touch-screen interfaces, have become part of the everyday usage items of many information consumers across the globe. However, it is clear that the learning curve for touch-screen interfaces is steeper than what was expected. This presents some problems especially along with the current trend towards designing more complex mobile applications. The objective of this research was to determine how users interact with applications on touch-screen mobile devices, and how they progress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In addition, there are as yet no established gesture guidelines for smartphone applications [38,40]. Therefore, Help and documentation and/or first time user tutorials may offer a way for new users to learn how to use a smartphone application [27].…”
Section: Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are as yet no established gesture guidelines for smartphone applications [38,40]. Therefore, Help and documentation and/or first time user tutorials may offer a way for new users to learn how to use a smartphone application [27].…”
Section: Investigationmentioning
confidence: 99%
“…Therefore, Help and documentation and/or first time user tutorials may offer a way for new users to learn how to use a smartphone application [27]. This is echoed by research that has suggested that many first time users will avail of tutorials to some extent [39,40].…”
Section: Investigationmentioning
confidence: 99%